Diet Composition and Nutritional Niche Breadth Variability in Juvenile White Sharks (Carcharodon carcharias) - Grainger, Richard; Peddemors, Victor M.; Raubenheimer, David; Machovsky-Capuska, Gabriel E. (Frontiers in Marine Science, 2020)
Establishing diets and dietary generalism in marine top predators is critical for understanding their ecological roles and responses to environmental fluctuations. Nutrition plays a key mediatory role in species-environment interactions, yet descriptions of marine predators’ diets are usually limited to the combinations of prey species consumed. Here we combined stomach contents analysis (n = 40), literature prey nutritional data and a multidimensional nutritional niche framework to establish the diet and niche breadths of white sharks (Carcharodon carcharias; mean ± SD precaudal length = 187.9 ± 46.4 cm, range = 123.8-369.0 cm) caught incidentally off New South Wales (NSW), Australia. Our nutritional framework also facilitated the incorporation of existing literature diet information for South African white sharks to further evaluate nutritional niches across populations and sizes. Although teleosts including pelagic Eastern Australian Salmon (Arripis trutta) were the predominant prey for juvenile white sharks in NSW, the diversity of benthic and reef-associated species and batoids suggests regular benthic foraging. Despite a small sample size (n = 18 and 19 males and females, respectively), there was evidence of increased batoid consumption by males relative to females, and a potential size-based increase in shark and mammal prey consumption, corroborating established ontogenetic increases in trophic level documented elsewhere for white sharks. Estimated nutritional intakes and niche breadths did not differ among sexes. Niche breadths were also similar between juvenile white sharks from Australia and South Africa. An increase in nutritional niche breadth with shark size was detected, associated with lipid consumption, which we suggest may relate to shifting nutritional goals linked with expanding migratory ranges.